Does testosterone predict women's preference for facial masculinity? - Marcinkowska UM; Helle S; Jones BC; Jasienska G (PUBLIC LIBRARY SCIENCE, 2022)
The influence of sex hormones on women's mate preferences has been an intensively discussed topic for more than a decade. Yet the extent to which levels of sex hormones, and testosterone in particular, influence women's mate preferences is unclear. Thus, the current study used multilevel modelling to investigate putative relationships between salivary testosterone and facial masculinity preferences in a sample of 68 women, while controlling for their age, partnership status, and sociosexuality. We found no significant associations between masculinity preferences and either individual differences or within-woman changes in testosterone. We did find however, that sociosexuality was positively correlated with masculinity preferences. Although it has previously been suggested that testosterone is related to women's facial masculinity preference, our data do not support this proposal.